Effect of a clinical skills refresher course on the clinical performance, anxiety and self-efficacy of the final year undergraduate nursing students. (November 2017) - Shahsavari, Hooman; Ghiyasvandian, Shahrzad; Houser, Marian L.; Zakerimoghadam, Masoumeh; Kermanshahi, Seyedeh Sosan Nouri; Torabi, Sedigheh
Abstract: Although the final year of nursing undergraduate programs that focus on clinical education are planned to prepare nursing students to better transition to the real world of health care service; evidence has shown that this program is not sufficient to reach this end goal. This controlled trial study was to investigate the effectiveness of a basic clinical skills refresher course for nursing students before entering the internship program. The sample consisted of 160 undergraduate nursing students assigned into two groups. The intervention was a three-day refresher course directed by nurse instructors for intervention group focused on 10 basic nursing procedures in the clinical skill lab. The control group did not receive any intervention. The students' anxiety, clinical self- efficacy and clinical skills practice were measured before and after intervention in both groups. The results indicated that the students who took part in the refresher course experienced lower anxiety levels, higher levels of clinical self-efficacy, and have better clinical skills during their internships. The undergraduate nursing curriculum can be strengthened by the basic clinical skills refresher course. This refresher course can bridge the theory - practice gap and provide a better transition from the student to nurse role. Highlights: Nursing curriculum can be strengthened through the clinical skills refresher course. The clinical skills refresher course can reduce students' anxiety for nursing practice. The clinical skills refresher course can increase students' clinical self-efficacy. The clinical skills refresher course can promote nursing students' clinical abilities. The clinical skills refresher course can bridge the nursing theory – practice gap.